Multi-stage phononic crystal structure for anchor-loss reduction of thin-film piezoelectric-on-silicon microelectromechanical-system resonator. (25th May 2018) - Bao, Fei-Hong; Bao, Lei-Lei; Li, Xin-Yi; Khan, Muhammad Ammar; Wu, Hua-Ye; Qin, Feng; Zhang, Ting; Zhang, Yi; Bao, Jing-Fu; Zhang, Xiao-Sheng
Abstract: Thin-film piezoelectric-on-silicon acoustic wave resonators are promising for the development of system-on-chip integrated circuits with micro/nano-engineered timing reference. However, in order to realize their large potentials, a further enhancement of the quality factor ( Q ) is required. In this study, a novel approach, based on a multi-stage phononic crystal (PnC) structure, was proposed to achieve an ultra-high Q . A systematical study revealed that the multi-stage PnC structure formed a frequency-selective band-gap to effectively prohibit the dissipation of acoustic waves through tethers, which significantly reduced the anchor loss, leading to an insertion-loss reduction and enhancement of Q . The maximum unloaded Q u of the fabricated resonators reached the value of ∼10, 000 at 109.85 MHz, indicating an enhancement by 19.4 times.